Psycho-behavioral intervention model for effective sustainable awareness in green development - Yaman, Rostam; Kespanerai, Kokchang; Ahmad, Noraini; Ismail, Farrah Zuhaira (EDP Sciences, 2019)
This research addressed an appropriate way to promote sustainable behavior by intervening in psycho-behavioral awareness to promote green inclination psychological characteristics. The main objective of this study aimed to determine the effectiveness of a psycho-behavioral intervention model on the occurrence of sustainable awareness and positive behavior in tertiary education students. A pre-test and post-test control group design provided an understanding of the extent to which psychological characteristics can have an impact on 220 interior architecture students in increasing sustainable awareness and positive behavior after the training. The major finding indicated that interior architecture students who received the psycho-behavioral intervention model gained greater psychological characteristics and sustainable awareness and also showed greater positive behavior than the control group after training. It can be concluded that psycho-behavioral intervention can promote sustainable awareness and positive behavior.